Leading the life you want : skills for integrating work and life - Friedman, Stewart D. (Boston, Massachusetts : Harvard Business Review Press, 2014)
"Must professional accomplishments come at the expense of having a full life? Not according to Wharton professor and leadership and work-life expert Stewart D. Friedman. In his new book, Friedman identifies critical skills for leading an authentic and balanced life, and illustrates them through the compelling stories of six remarkable high-profile people. He also shows how to develop and apply each skill through a series of exercises anyone can use. Each leader showcased in the book-Bruce Springsteen, Michelle Obama, Sheryl Sandberg, Tom Tierney, Eric Greitens, and Julie Foudy-exemplifies a specific set of skills for achieving greater harmony between work and life. Friedman identifies these discrete skills-for being real, being whole, and being innovative-that reduce conflict. Then, based on in depth interviews and research, he paints a dramatic picture of the creative ways these six very different leaders pursue authenticity and harmony every day. Friedman also includes exercises for practicing each skill, along with actionable ideas curated from research in organizational psychology and related fields, for applying them. This book will inspire and reinforce the changes people want to make to lead more balanced lives and to become better leaders"--
"What do Bruce Springsteen, Michelle Obama, Sheryl Sandberg, Tom Tierney, Eric Greitens, and Julie Foudy have in common? Each one of these men and women shows that accomplishment in a career doesn't have to come at the expense of having a full life. And each one of these leaders exemplifies a set of skills--whether applied consciously or not--for achieving greater harmony between work and life. In this book, author Stewart D. Friedman tells their stories and, through them, shows everyday people how to apply the critical skills for leading an authentic and balanced life. Picking up where Total Leadership leaves off, Friedman first identifies the discrete skills--for being real, being whole, and being innovative--that reduce conflict between work and life. Then, based on in-depth interviews and research, he paints a dramatic picture of the creative ways these six, and very different, leaders pursue authenticity and harmony in work and life. Describing the specific skills each one uses, Friedman provides a set of exercises for practicing each skill, along with concrete, actionable ideas curated from research in organizational psychology and related fields for applying them. Emphasizing the actions that make life better--and that contribute to great leadership--this book will inspire and reinforce the changes people want to make to lead more balanced lives"--
Includes bibliographical references (pages 223-241) and index.
Print version record.
Keywords: Work-life balance; Work and family; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Motivational; Work and family; Work-life balance; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; elektronické knihy; electronic books